Advocacy for Couples and Families: New Directions APA Publication Manual (7th Edition). (July 2020) - Noble, Nicole; Bradley, Loretta; Hendricks, Bret
The 7th edition APA Publication Manual ( Manual ) was released in October 2019. The significant changes between the 6th edition and 7th edition of the Manual were described in a previous issue of The Family Journal: Counseling and Therapy for Couples and Families . This article is written to expand on the substantial changes to the Manual ' s guidelines and to focus on bias-free language and inclusivity. Using the International Association of Marriage and Family Counselors Code of Ethics as a cornerstone, this article will focus on such diverse issues as advocacy, bias-free language, gender, inclusivity, racial/ethnic identity, sensitivity (avoiding labels), socioeconomic, and intersectionality issues. Recommendations are made, and examples are provided to help couple and family counselors become cognizant of the changes.